PENINGKATAN KEMAMPUAN KADER MELALUI PELATIHAN SEBAGAI UPAYA DETEKSI DINI DAN PENCEGAHAN STUNTING DI DESA RANAH SINGKUANG KABUPATEN KAMPAR - Sari, Septi Indah Permata; Harahap, Juraida Roito; Erowati, Dewi (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2023)
Abstract Stunting is a nutritional problem caused by chronic lack of nutritional intake over a long period of time starting in the first 1000 days of life (HPK), resulting in growth disorders in children. This disorder means that the child's height is lower or shorter (stunted) than the age standard, the child's weight and the child's motor skills. Kampar Regency is one of the districts in Riau Province which has stunting locus villages in 2019, with a prevalence of 32.05% of stunted toddlers. Ranah Singkuang Village is a village supported by the Riau Ministry of Health Poltekkes since 2020. Ranah Singkuang Village is 1 of 10 villages designated as a Stunting Locus since 2019. In 2020 it shows that there has been an increase in stunted toddlers in the last year, from 2019 to 2020 in 3 villages , one of which is Ranah Singkuang Village. The aim of this activity is to increase cadres' knowledge and skills in preventing and handling stunting. This activity was carried out offline for 19 cadres. The activity was carried out in 4 meetings, with the result that the average knowledge of cadres about stunting increased from the initial 60.66 to 90.66 with the lowest post test score being 70 and the highest being 90. This means that there was an increase in cadres' knowledge after being given health education and training. The results of the analysis of the implementation of community service activities show that there is a difference between knowledge before the training is carried out and after the training is carried out.